Exploring the correlation between corrective glucose treatment and long-term patient outcomes: a SHINE secondary analysis - Paul Horton; Vishal Patel; C. L. Hall; Karen C. Johnston; Yajun Mei; Ofer Sadan (Frontiers in Neurology)
IntroductionGlucose control is an important aspect of acute ischemic stroke management. Although absolute glucose concentration remains the focus in clinical stroke care, glucose variability is increasingly recognized as a viable treatment target. To assess the relationship between acute post-stroke glycemic control parameters and patient outcomes, we reanalyzed the data from the first 8 h of treatment for patients in the Stroke Hyperglycemia Insulin Network Effort (SHINE) clinical trial, when glycemic variability is highest.MethodsIn this secondary analysis of the SHINE dataset, the rate of glucose change during the first 8 h was evaluated for its association with patient outcomes, dichotomized as modified Rankin scale (mRS) 0–2 versus 3–6, using logistic regression and a linear mixed-effects model.ResultsUnadjusted analysis of the glucose correction period during the first 8 h suggested that patients with mRS 3–6 had a faster glucose correction compared to those with mRS 0–2 (−8.9 and −6.7 mg/dL/h, p < 0.001). This finding remained statistically significant in both the intensive intervention group and the poorly controlled diabetic sub-group (glycosylated hemoglobin [HbA1c] ≥ 6.4). Mixed-effects models also indicated a significant difference in the rate of glucose change (1.9 mg/dL/h, p < 0.001) between outcome groups (mRS 0–2 versus 3–6) across both treatment and HbA1c sub-groups.ConclusionAnalysis of the first 8 h of the SHINE data suggests that early, rapid correction of glucose is associated with poor outcomes, particularly in the sub-group of patients with HbA1c ≥ 6.4. Further research is warranted to assess early glycemic correction as a possible personalized glucose management goal.